Synchrotron-based infrared microspectroscopy under high pressure: An introduction - Lingping Kong (AIP Publishing LLC, 2021)
Synchrotron sources with high photon flux, small source size, and broad energy range have revolutionized ultrafine characterization of condensed matter. With the addition of the pressure dimension realized by the use of diamond anvil cells, enormous progress has been achieved throughout high-pressure science. This is particularly so for synchrotron-based infrared microspectroscopy (SIRMS) with its very high signal-to-noise ratio, high spatial resolution, and extended measurement conditions. SIRMS has high sensitivity, providing a platform for the investigations of the very small amounts of material that need to be used in high-pressure research. This review summarizes developments in SIRMS, focusing on instrumentation and high-pressure measurements. Applications to measurements of infrared reflectance and absorption are presented, illustrating how SIRMS results play a crucial role in advancing understanding of the crystalline phase transitions, electronic transitions, metallization, lattice dynamics, superconductivity, and novel functional behavior. New insights into spectroscopic properties, together with some cutting edge issues and open problems, are also briefly discussed.